How multimedia computers work (Mindscape, Inc., 1994)
This CD-ROM along with Zip Data, a colorful animated host, help you see how each part of your computer works, how it processes data, where the RAM and ROM chips are located, and how an electronic gun lights your monitor. Included are more than 50 detailed 3-D computer part animations with narration, original, fully orchestrated music and sound effects. Also included are eight different computer tours, a word glossary of computer terms, answers to common computer questions, and Windows tips.